Author’s Neologisms in the Contemporary Bulgarian Press - Зидарова, Ваня (Poznańskie Studia Slawistyczne, 2015)
Author’s neologisms (so-called occasionalisms) are characteristic phenomena of the contemporary Bulgarian press. They are present in all components of the publishing text. Their purpose is to bring attractiveness in speech, voice the author’s point of view in an expressive way, characterize the  referent  and  attract  the  attention  of  the  reader. Author’s  neologisms  are  manifestations  of linguistic play and are based on the current literary word-formation rules. They are characterized by low frequency but high expressiveness. For this purpose, we use the creative possibilities of graphics, fonts, morphology, phonetics, semantic transposition.